Shareholding control, corporate governance and debt financing of Brazilian firms - Brandão, Isac de Freitas; Crisóstomo, Vicente Lima (Review of Business Management, 2024)
Purpose – This study investigates the effect of shareholding control and corporate governance on access to debt financing by Brazilian firms. Theoretical framework – From the perspective of Agency Theory, the presence of controlling shareholders can contribute to a preference for debt financing. On the other hand, strengthening the internal corporate governance system can reduce agency conflicts and facilitate access to the credit market. Design/methodology/approach – Using mean difference tests and regression analysis, we analyzed the relationship between debt financing, shareholding control and corporate governance of 168 firms listed on B3 in the period 2011-2019. Findings – Debt financing is related to shareholding control, being higher in firms with majority control and lower in firms with dispersed control. The quality of corporate governance contributes to access to debt, especially in firms with shared control. However, in firms with dispersed control, the relevance of corporate governance is lower. Research Practical & Social implications – The evidence reiterates the importance of strengthening the internal governance system of Brazilian firms as a way of improving access to the credit market, considering their ownership structure, especially the type of shareholding control. Originality/value – The paper shows that shareholding control, as an attribute of the ownership structure and a determinant of agency conflicts, can influence corporate financing decisions and the relationship between the adoption of corporate governance practices and access to debt financing.